Outcomes and Cost Analysis of Virtual Fracture Clinic Management of 5th Metatarsal Base Fractures. Issue 1 (January 2022) - Zahan, Nusrat; Patel, Amit; Atkinson, Kate; Jha, Shilpa; Heidari, Nima; Parker, Lee; Vris, Alexandros; Romans, Francesc Malagelada; Jeyaseelan, Luckshmana A.
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Overwhelming demand for trauma services with increasing emergency department (ED) attendances, has increased pressure on fracture clinics in many units, with this demand exceeding capacity. Virtual fracture clinics (VFCs) have been shown to be safe and cost-effective in many specialties. Optimal treatment of 5th metatarsal base fractures remains controversial. Complications of base of 5th metatarsal fractures include delayed union and painful mal/non-union. Surgical fixation has been shown to enable faster return to sport, with lower faster union times and lower non-union rates than conservative management. The aims of this study were to assess whether the management of 5th metatarsal base fractures using a VFC model is safe, cost-effective and accceptable to the patients, whilst avoiding undesirable outcomes. Methods: All patients presenting to the VFC at our major trauma centre, with a 5th metatarsal base fracture between January 2019 and December 2019 were included in the study. One hundred and thirty six patients were identified. All patients had a standardised VFC treatment protocol including full weight bearing in a walker boot, rehabilitation planning to wean out of the boot and advice to contact the unit for follow-up if ongoing pain after 4 months. Minimum follow-up was one year. Patient records were retrospectively reviewed for baseline demographic data, including co-morbidities and smoking history. Overall complication rates, including mal and non-union as well as operative intervention rates were noted. Patients from the cohort who required face to face appointments were identified and the cause for return was identified. A cost analysis was also performed to evaluate the financial implications of the service. Results: Mean age was 41, 6 years (18-92). Average time from ED attendance to VFC review was 2 days (1 - 5). Fractures were classified according to the Torg Classification with 106 (78%) Type 1 fractures, 15 (11%) Type 2 fractures and 15 (11%) Type 3 fractures. At VFC, 135/136 (99.2%) were discharged with the appropriate 5th metatarsal base fracture protocol. Twelve patients (8.8%) arranged further follow-up after initial discharge. The most common reason for return was ongoing pain (6/8 - 75.0%). This subgroup of the patients required an average of 3 (1-6) further appointments. There was 1 non-union during the study period. Based on 2 face to face visits on a traditional pathway, 248 clinic visits were saved with an approximate cost saving of nearly £40, 000 ($55, 500). Conclusion: Our study supports the management of 5th metatarsal base fractures in the VFC setting. We have shown that the VFC model, with well a defined protocol is both safe and cost effective. Fifth metatarsal base fractures have good outcomes with conservative management, removing the traditional need to have in-person clinic visits to confirm the diagnosis, management and prognosis.